Evaluation of inferior mesenteric vein drainage patterns in the Turkish population: A multidetector computed tomography study: Inferior mesenteric vein drainage patterns - Yilmaz, Hakan (Journal of Surgery and Medicine, 2023)
Background/Aim: The inferior mesenteric vein (IMV) plays a crucial role in the venous system as it joins the superior mesenteric vein (SMV) and splenic vein to form the portal vein. The widespread adoption of multidetector computed tomography (MDCT) has greatly enhanced our ability to assess abdominal vascular structures. This study aimed to investigate the IMV drainage patterns in a Turkish population using MDCT. Methods: This descriptive, single-center, retrospective study included patients who had undergone abdominal computed tomography (CT) in the portal phase at our hospital for various clinical indications. Excluded from the study were patients who did not undergo imaging in the portal venous phase, those with incomplete evaluation of all IMV segments, and individuals who had undergone pancreaticoduodenal or intestinal surgery for any reason. We retrospectively analyzed a total of 877 contrast-enhanced MDCT examinations performed at our hospital between March 2022 and March 2023. Patients were classified based on their IMV drainage patterns into the following categories: type 1 (drainage into the splenic vein), type 2 (drainage into the SMV), type 3 (drainage at the junction level), type 4 (drainage into the branches of the SMV), and type 5 (patients in whom IMV assessment was not possible). Results: The mean age of the patients was 48.7 years (range: 24–92 years), with 449 (51.2%) being male and 428 (48.8%) female. The distribution of patients according to IMV drainage patterns was as follows: type 1, n=379 (43.2%); type 2, n=398 (45.4%); type 3, n=71 (8.1%); type 4, n=15 (1.7%); and type 5, n=14 (1.6%). Conclusion: Our study findings indicate that in the Turkish population, the IMV predominantly drains into the SMV before joining the splenic vein. This disparity from certain studies in the literature underscores the variability in IMV drainage patterns, emphasizing the importance of individualized patient evaluation in this regard.